Bathymetry-constrained impact of relative sea-level change on basal melting in Antarctica - M. Kreuzer; M. Kreuzer; T. Albrecht; T. Albrecht; L. Nicola; L. Nicola; R. Reese; R. Reese; R. Winkelmann; R. Winkelmann; R. Winkelmann (The Cryosphere)
Relative sea level (local water depth) on the Antarctic continent is changing through the complex interplay of processes associated with glacial isostatic adjustment (GIA). This involves near-field viscoelastic bedrock displacement and gravitational effects in response to changes in Antarctic ice load but also far-field interhemispheric effects on the sea-level pattern. On glacial timescales, these changes can be of the order of several hundred meters, potentially affecting the access of ocean water masses at different depths to Antarctic grounding lines and ice-sheet margins. Due to strong vertical gradients in ocean temperature and salinity at the continental-shelf margin, basal melt rates of ice shelves have the potential to change just by variations in relative sea level alone. Based on simulated relative sea-level change from coupled ice-sheet–GIA model experiments and the analysis of topographic features such as troughs and sills that regulate the access of open-ocean water masses onto the continental shelf, we derive maximum estimates of Antarctic basal melt rate changes, solely driven by relative sea-level variations. Our results suggest that the effect of relative sea-level changes on basal melting is limited, especially compared to transient changes in the climate forcing.